Corneal Biomechanical Properties in Myopic Eyes Measured by a Dynamic Scheimpflug Analyzer - Jingyi Wang; Ying Li; Yumei Jin; Xue Yang; Chan Zhao; Qin Long (Journal of Ophthalmology)
Purpose. To evaluate the corneal biomechanical parameters in myopic and emmetropic eyes using Corneal Visualization Scheimpflug Technology (CorVis ST). Methods. 103 myopic and emmetropic eyes of 103 patients were examined. Corneal biomechanical parameters, axial length, and mean keratometry were measured using CorVis ST, IOL Master, and topography, respectively. Corneal biomechanical properties were compared within four groups. Bivariate correlation analysis was used to assess the relationship between corneal biomechanical parameters and ocular characteristics. Results. Four of ten corneal biomechanical parameters, namely, deformation amplitude (DA), first- and second-applanation time (A1-time, A2-time), and radius at highest concavity (HC radius), were significantly different within the four groups (P<0.05). In correlation analysis, DA was positively correlated with axial length (r=0.20, P=0.04); A2-time was positively correlated with spherical equivalent (SE) (r=0.24, P=0.02); HC radius was positively correlated with SE (r=0.24, P=0.02) and was negatively correlated with mean keratometry (r=-0.20, P=0.046) and axial length (r=-0.21, P=0.03). Conclusions. The corneal refraction-related biomechanical alterations were associated with ocular characteristics. Highly myopic eyes exhibited longer DA and smaller HC radius than do moderately myopic eyes; the eyes with longer axial length tend to have less corneal stiffness and are easier to deform under stress.